Regional Patterns of Gene Expression in Human and Chimpanzee Brains - Khaitovich, Philipp; Muetzel, Bjoern; She, Xinwei; Lachmann, Michael; Hellmann, Ines; Dietzsch, Janko; Steigele, Stephan; Do, Hong-Hai; Weiss, Gunter; Enard, Wolfgang; Heissig, Florian; Arendt, Thomas; et al.

(untitled) (Genome Research, 2004)
We have analyzed gene expression in various brain regions of humans and chimpanzees. Within both human and chimpanzee individuals, the transcriptomes of the cerebral cortex are very similar to each other and differ more between individuals than among regions within an individual. In contrast, the transcriptomes of the cerebral cortex, the caudate nucleus, and the cerebellum differ substantially from each other. Between humans and chimpanzees, 10% of genes differ in their expression in at least one region of the brain. The majority of these expression differences are shared among all brain regions. Whereas genes encoding proteins involved in signal transduction and cell differentiation differ significantly between brain regions within individuals, no such pattern is seen between the species. However, a subset of genes that show expression differences between humans and chimpanzees are distributed nonrandomly across the genome. Furthermore, genes that show an elevated expression level in humans are statistically significantly enriched in regions that are recently duplicated in humans.